Differentiation between emerging non-steroidal and established steroidal mineralocorticoid receptor antagonists: head-to-head comparisons of pharmacological and clinical characteristics. (2nd November 2021) - Barrera-Chimal, Jonatan; Kolkhof, Peter; Lima-Posada, Ixchel; Alexandre, Joachim; Rossignol, Patrick; Jaisser, Frederic
ABSTRACT: Introduction: Mineralocorticoid receptor (MR) antagonists (MRAs) provide cardiorenal protection. However steroidal MRAs might induce hyperkalemia and sex hormone-related adverse effects. Several novel non-steroidal MRAs are being developed that are highly selective for the MR and may have an improved safety profile. Areas covered: This narrative review summarizes data from head-to-head comparisons of emerging non-steroidal MRAs with older steroidal MRAs, including pharmacological characteristics, pharmacokinetic properties, clinical outcomes, and safety, and highlights similarities and differences between emerging agents and established steroidal MRAs. Expert opinion: Head-to-head comparisons in phase 2 trials suggest that the new non-steroidal MRAs exhibit at least equivalent efficacy to steroidal MRAs but may have a better safety profile in patients with heart failure and/or kidney disease. When also taking into account data from recent phase 3 placebo-controlled trials, these novel non-steroidal MRAs have the potential to provide a cardiorenal benefit above that of current optimized standard-of-care treatment in a high-risk population with reduced renal function, and with a lower risk of hyperkalemia. To optimize therapy, further research is needed to clarify the molecular differences in the mode of action of non-steroidal MRAs versus steroidal MRAs, and biomarkers that are predictive of MRA response need to be identified and validated.